(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
The present study deals with the demographics of the fatal cases of cranio-cerebral injuries occurring in the rural parts of Central India. The present study was carried out at Mahatma Gandhi Institute of Medical Sciences, Sevagram, District-Wardha during the period of October 2002 to September 2004. All consecutive cases of fatal medico-legal cranio-cerebral injuries were included in present study. The details about age, sex, time of injury, time of mortality, type of vehicle were carefully studied and filled in a predesigned proforma. There were a total 150 cases (rural residential address-124 cases, urban residential address-26 cases) of fatal head injuries in the present study, 78% male and 22% were female. Most of the cases (56.6%) of fatal head injuries were young adults in the age group of 21-40 years. Most of the fatalities (51.33%) because of head injuries were within 24 hours and it was worrisome that 24 (16.7%) cases expired at the scene of accident. Due to a combination of factors, including rapid motorization, poor road and traffic infrastructure as well as the behavior of road users, the